Autecology of Amorphophallus gigas in Batang Natal Watershed, North Sumatra, Indonesia - RIDAHATI RAMBEY; RAHMAWATY RAHMAWATY; MOHD NAZIP SURATMAN; ABDUL RAUF; ESTHER SORTA MAULI NABABAN; DELVIAN DELVIAN; T. ALIEF ATHTHORICK; MOHD HASMADI ISMAIL; SECA GENDASECA (Society for Indonesian Biodiversity, 2024)
Abstract. Rambey R, Rahmawaty, Suratman MN, Rauf A, Nababan ESM, Delvian, Aththorick TA, Ismail MH, Gendaseca S. 2024. Autecology of Amorphophallus gigas in Batang Natal Watershed, North Sumatra, Indonesia. Biodiversitas 25: 2887-2900. Amorphophallus gigas Teijsm. & Binn., a member of the Araceae family, is distributed across Sumatra, particularly within the Batang Natal watershed of Mandailing Natal District. This plant population thrives significantly under the forest canopy in high-humidity environments, such as a watershed, despite being exposed to certain challenges. The Batang Natal Watershed, spanning 70.5 km and originating in the Batang Natal Sub-district, is frequently subjected to mining activities. Therefore, this study aimed to explore the autecology of A. gigas in the watershed, focusing on factors such as occurrence, associated plant species, vegetation composition, and soil characteristics. The occurrences of A. gigas were identified through direct interviews with the local community, complemented by field collection of coordinate points in five villages. The vegetation around A. gigas habitats was then analyzed using nested sampling with a plot size of 1 ha. There was no A. gigas in Aek Garingging Village despite the reported presence in 2020, while there were nine individuals in each village of Rao-Rao and Lubuk Bondar Panjang and six and three individuals in Bangkelang and Aek Nangali, respectively. There were 63 tree and 39 understory species recorded around the A. gigas habitat. Lubuk Bondar was dominated by Hevea brasiliensis (Willd. ex A.Juss.) Müll.Arg. across several strata, with generally low to very low associations. Bangkelang was characterized by Gmelina arborea Roxb. ex Sm. in the pole and tree strata, with similarly low associations. In Rao-Rao, Coffea canephora Pierre ex A.Froehner was prominent in the seedling and sapling strata, showing low but consistent associations, and Selaginella willdenowii (Desv.) Baker in the understorey had a high positive association. The dominant species in each site typically had low to very low associations with other species, indicating limited ecological connectivity with A. gigas. The spatial distribution of A. gigas suggested a clumped pattern to ensure A. gigas preservation in the Batang Natal Watershed, it is essential to designate the plant's natural habitat as an in situ conservation area.